Aftershock Hazard Assessment Based on Utilization of Observed Main Shock Demand. Issue 2 (May 2018) - Muderrisoglu, Ziya; Yazgan, Ufuk
This paper presents an aftershock hazard assessment method that is based on taking into account the macroseismic indicators of the main shock observed at the site. The proposed method is referred to as conditional aftershock hazard assessment (CAHA). The essence of the CAHA method is to estimate the aftershock hazard at the site conditioned on the main shock intensity exhibited at that location. This is achieved by exploiting the correlation between the ground motion intensities exhibited during the main shock and the aftershock events. Specifically, the correlation of the epsilons registered for the two events, is utilized. Investigation of the epsilon correlation indicates that highest correlation occurs at the range of periods between 0.8 and 1.0 s. Based on the estimated epsilon correlation, the mean and the dispersion of the aftershock ground motion intensity, are estimated. An application of the proposed method to a set of sites affected by the 2011 Van (Turkey) M w 7.2 earthquake sequence is illustrated. The performance of the method is assessed in comparison with the conventional approaches. For the considered example application, the hazard estimated using the proposed method shows a better agreement with the actual aftershock recordings, compared to the existing approaches.